DIURNAL VARIATIONS OF RENAL FUNCTION IN CONGESTIVE HEART FAILURE - VILLARREAL, H; SIROTA, J H; BALDWIN, D S (NEW YORK MEDICAL COLLEGE, NYC, EUA, 1927)
The escarpment region between Xilitla, San Luis Potosi, and Orizaba, Veracruz, is descr and its climate compared with that of the mts of S C The Mexican area has equal or greater rainfall but the extremes of temp are not so great The vegetation incl
PROC SOC EXP BIOL MED
Keywords: VARIATIONS, RENAL, FUNCTION, CONGESTIVE, HEART, FAILURE; CIENCIAS MEDICAS; MEDICINA INTERNA; NEFROLOGIA